Preparation of polyethersulfone / mesoporous silica interpenetrating network structure composite membrane and application of polyethersulfone / mesoporous silica interpenetrating network structure composite membrane in basic diffusion dialysis

By using polyether sulfone and mesoporous silica nanoparticle composite membrane in basic diffusion dialysis, the in-situ crosslinking copolymerization method and adjustment of monomer ratios has been solved by the difficulty in finding ion selectivity and flux in the prior art. The problem of appropriate compromises has achieved efficient separation of hydroxide and tungstate ions.

CN119386681APending Publication Date: 2025-02-07ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411746623.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to find a suitable compromise between ion selectivity and flux in basic diffusion dialysis, resulting in low efficiency of composite membranes in the separation of hydroxide and tungstate ions.

Method used

Compound cation exchange membranes were prepared by mixing polyethersulfone with mesoporous silica nanoparticles by in situ crosslinking copolymerization, and the ratio of acrylic acid and sodium parastyrene sulfonate was adjusted to optimize the ion flux and selectivity. balance.

Benefits of technology

The selective separation of composite membranes is achieved in alkaline diffusion dialysis. The hydroxide dialysis coefficient is between 0.00982m/h-0.01345m/h and the separation coefficient is between 26.2-36.0, which significantly improves the separation efficiency of the membrane. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386681A_ABST
    Figure CN119386681A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a polyethersulfone / mesoporous silica interpenetrating network structure composite membrane, which comprises the following steps: uniformly mixing polyethersulfone with monomer acrylic acid, sodium p-styrenesulfonate and mesoporous silica nanoparticles, performing in-situ polymerization to obtain a membrane liquid, defoaming, and volatilizing a solvent to obtain a composite cation exchange membrane. The polyethersulfone / mesoporous silica interpenetrating network structure composite membrane is used for separating hydroxyl ions and tungstate ions in a diffusion dialysis mode, the dialysis coefficient of the hydroxyl ions is 0.00863 m / h to 0.01345 m / h, and the separation factor (S) is 15.6 m / h to 36.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane separation, and in particular relates to the preparation of a polyethersulfone / mesoporous silica interpenetrating network structure composite membrane and its application in alkaline diffusion dialysis. Background Art

[0002] The rapid development of modern economy and the continuous advancement of industrialization have brought convenience to human life, but the pollution problem of industrial wastewater has also become increasingly prominent. For most developing countries, water pollution has become an important social issue related to the national economy and people's livelihood. Therefore, the development of an economical, efficient and environmentally friendly sewage treatment technology has always been a hot issue that researchers have been concerned about.

[0003] Membrane separation technology is a new technology that is simple, convenient, low-energy, environmentally friendly, low-cost and highly efficient. In recent years, it has received more and more attention in the treatment of water pollution. The core component of the diffusion dialysis process is the ion exchange membrane. Depending on the use environment, the membrane used needs to have long-term stability under the corresponding acidic / alkaline conditions, suitable water content and good ion selective permeability.

[0004] Interpenetrating polymer network (IPN) structure is a polymer blend with forced compatibility and coordination effect formed by two or more polymers with different chemical properties or incompatible in thermodynamics through cross-linking or intertwining. IPN technology has a wide range of applications and many types of technologies. We can select the appropriate IPN technology, change the type and ratio of polymers according to needs to obtain the required polymer composite materials.

[0005] Polyethersulfone (PES) has excellent heat resistance, physical and mechanical properties, insulation properties, etc., especially it can be used continuously at high temperature and can maintain stable performance in an environment with rapid temperature changes. It has been widely used in many fields. Due to its excellent thermal stability, acid-base stability, excellent oxidation resistance and good mechanical strength, it has become a popular polymer and has been widely used in the field of membrane separation. Dhiyaa et al. [reference Journal of Membrane Science, 659 (2022)] modified the surface of SiO2NPs by grafting a PEI layer, aiming to consolidate the weak interaction between NPs and polymer chains. Better compatibility means minimal agglomeration and ultimately higher membrane performance. The results show that the performance of the membrane was significantly improved after the incorporation of nano-additives. After SiO2-g-PEI modification, the hydrophilicity, porosity and permeability of the modified membrane were greatly improved, reaching the optimal value at 0.7 wt%. When 0.7 wt% SiO2-g-PEI was added, the removal rate of BSA increased to about 97%, while the removal rate of the unmodified membrane was 79%. Vikrant [Journal of Membrane Science, 603 (2020)] et al. successfully synthesized a composite cation exchange membrane based on S-MoS2 / SPES and investigated its applicability for electrodialysis desalination and diffusion dialysis alkali recovery. Flower-like molybdenum disulfide was prepared by hydrothermal sulfonation. Compared with the SPES membrane, the physicochemical and electrochemical properties of the composite membrane were significantly improved. The ionic conductivity of the DES-5 composite membrane is 1.95±10 -2 S / cm, and the ion exchange capacity is 1.42 meq / g, which is much higher than that of DES membrane. The desalination performance of the prepared membrane was evaluated from the aspects of power consumption and current efficiency. The power consumption of DES-5 composite membrane is 0.98 kWh / kg, which is 22% lower than that of DES membrane (1.26 kWh / kg); the current efficiency of DES-5 composite membrane is 69.47%, which is 28% higher than that of DES membrane (54.43). The separation factor of DES-5 in diffusion dialysis is 60.32. However, with the addition of S-MoS2 content, the ion flux of the composite membrane is not significantly improved. The present invention firstly functionalizes polyethersulfone by in-situ cross-linking copolymerization of two monomers with polyethersulfone, and prepares a composite cation exchange membrane with mesoporous silica to find a suitable compromise between ion selectivity and flux. Summary of the invention

[0006] The object of the present invention is to provide a preparation method of a polyethersulfone / mesoporous silica interpenetrating network structure composite membrane and its application in alkaline diffusion dialysis to improve the selective separation of the composite membrane. The hydroxide permeability coefficient (U OH-) is 0.00982m / h-0.01345m / h, and the separation coefficient is (S) 26.2-36.0.

[0007] The invention discloses a method for preparing a polyethersulfone / mesoporous silica interpenetrating network structure composite membrane, comprising the steps of uniformly mixing polyethersulfone (PES) with monomers of acrylic acid (AA), sodium p-styrene sulfonate (SSNa) and mesoporous silica (MS) nanoparticles, polymerizing the mixture in situ to obtain a membrane solution, and then degassing and volatilizing the solvent to obtain a composite cation exchange membrane.

[0008] The specific steps include: Step 1: Preparation of MS CTAB was used as a template agent, dissolved in a mixed solvent of water and ammonia, and TEOS was used as a silicon source. Mesoporous silica nanoparticles were obtained by reacting at 60°C for 2h, and the template agent CTAB was removed by high-temperature calcination in a muffle furnace.

[0009] The specific steps are as follows: 360 mL of deionized water and 11 mL of ammonia water are added to a 500 mL three-necked flask and mixed and stirred evenly, then 0.8 g of the template agent CTAB is added and stirred at room temperature until completely dissolved. After the solution is heated to 60°C, 4 mL of TEOS is added dropwise for about 10 min and magnetically stirred at 60°C for 2 h. Turn off the stirring and let it stand for 24 h. Finally, the obtained solution is centrifuged, filtered, and dried, and the obtained sample is calcined at 550°C in a muffle furnace for 6 h and placed in a dryer for use. The size of the MS prepared by the present invention is about 80 nm.

[0010] Step 2: Preparation of SPES membrane solution Monomer sodium p-styrene sulfonate and mesoporous silica were added to DMAc, and ultrasonic-assisted dispersion and dissolution were performed. After complete dissolution, acrylic acid, polyethersulfone, crosslinking agent N, N-methylenebisacrylamide and initiator azobisisobutyronitrile were added in sequence, and the reaction was stirred at 70°C in a nitrogen environment for 24 h.

[0011] The specific steps are as follows: weigh SSNa (1.0 g) and a certain amount of mesoporous silica, add them to DMAc (11 g), and dissolve and disperse them by ultrasound-assisted dissolution; then add AA (0.67 g), MBA (83.3 mg), AIBN (33.4 mg) and PES (2 g) to the above solution, heat it to 70°C, and stir the reaction for 24 h under N2 atmosphere to obtain a functionalized polyethersulfone solution.

[0012] Step 3: Preparation of composite cation exchange membrane The solution obtained in step 2 was placed in a vacuum oven and vacuumed at 25°C to remove bubbles. A 200 μm thick scraper was then used to scrape the film on a glass plate. The glass plate was finally heated on a hot plate at 60°C. After the solvent was completely evaporated, the prepared membrane was repeatedly washed with deionized water to remove unreacted monomers. Finally, the membrane was vacuum dried at 100°C for 12 h to obtain a SPES / MS cationic composite membrane.

[0013] In step 1, the muffle furnace calcination temperature is 550°C and the time is 6 h.

[0014] In step 2, the mass ratio of polyethersulfone, sodium p-styrenesulfonate and acrylic acid is 6: 3: 2, and the mass ratio of MS addition is 2%-8% (based on the total mass of PES, AA, and SSNa), such as 2%, 4%, 6%, and 8%.

[0015] The invention discloses an application of the polyethersulfone / mesoporous silicon oxide interpenetrating network structure composite membrane in alkaline diffusion dialysis.

[0016] Specifically, the polyethersulfone / mesoporous silica interpenetrating network structure composite membrane is used to separate hydroxide ions and tungstate ions by diffusion dialysis.

[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention introduces polyethersulfone into the alkaline diffusion dialysis separation membrane, and in-situ crosslinking copolymerization of two functional monomers with polyethersulfone not only provides ion exchange sites, but also improves the hydrophilicity of the membrane, promotes the transfer of hydrated ions, and is beneficial to OH - and WO4 2- separation.

[0018] 2. Based on existing research, the present invention adjusts the ratio of the two monomers, acrylic acid and sodium p-styrene sulfonate, and optimizes the compromise between ion flux and selectivity.

[0019] 3. Add mesoporous silica to prepare the composite membrane. The mesoporous structure of silica has water retention and can provide ion channels, effectively promoting the transfer of hydrated ions.

[0020] In summary, the prepared SPES / MS cationic composite membrane is applied to alkaline diffusion dialysis and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The schematic diagram of the synthesis route of functionalized polyethersulfone of the present invention is shown in FIG.

[0022] Figure 2 The infrared spectrum of SPES prepared by the present invention. Figure 2It can be seen that the characteristic peaks of carboxyl and sulfonic acid groups appear in the infrared spectrum, proving the successful modification of polyethersulfone.

[0023] Figure 3 The XPS elemental analysis diagram of the SPES / MS composite membrane prepared in the present invention. Figure 3 It can be seen that after adding silicon oxide, the Si element peak appears in the XPS spectrum of the composite film, proving the successful introduction of mesoporous silicon oxide.

[0024] Figure 4 This is a transmission electron microscope image of the mesoporous silicon oxide prepared in the present invention. Figure 4 It can be seen that mesoporous silica has an obvious mesoporous structure with a size of about 80 nm.

[0025] Figure 5 IEC diagrams of SPES membranes with different monomer ratios and SPES / MS composite membranes prepared by the present invention. Figure 5 It can be seen that the ion exchange capacity of the SPES membrane increases with the increase of SSNa ratio and decreases with the increase of mesoporous silica content.

[0026] Figure 6 Diffusion dialysis separation performance of cation exchange membranes with different monomer ratios and different MS contents prepared in Examples 1-9. Figure 6 It can be seen that the SPES membrane has the best separation effect when SSNa / AA:6 / 4. After adding mesoporous silica, the composite membrane with a mesoporous silica content of 6% has the best separation effect. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further analyzed and explained below through specific embodiments. Embodiment 1:

[0028] The specific experimental steps are as follows: (1) Preparation of SPES: SSNa (1.0 g) was weighed and added to DMAc (11 g), and then dissolved and dispersed by ultrasound-assisted dissolution. Then, AA (0.67 g), MBA (83.3 mg), AIBN (33.4 mg) and PES (2 g) were added to the above solution, the temperature was raised to 70 °C, and the reaction was stirred for 24 h under N2 atmosphere to obtain functionalized polyethersulfone (SSNa / AA: 6 / 4).

[0029] (2) Preparation of cation exchange membrane: The solution after the reaction in step 2 was placed in a 25°C vacuum oven and evacuated for 30 min to remove bubbles. The film was then scraped on a glass plate with a 200 μm thick scraper. The glass plate was placed on a 60°C heating table. After the solvent was completely evaporated, the prepared membrane was repeatedly soaked and cleaned with deionized water to remove unreacted monomers. Finally, the membrane was dried in a 100°C vacuum oven to obtain a SPES cation exchange membrane.

[0030] Performance Testing: Diffusion dialysis process: First, the membrane was immersed in a 1M NaOH / Na2WO4 mixed alkaline solution for 1 h to adapt it to the diffusion dialysis environment, then rinsed several times with deionized water and wiped with filter paper. The effective area used for the test was 6.0 cm 2 Then, 100 mL of deionized water and 100 mL of mixed alkali solution were added to the chambers on both sides of the membrane respectively. Driven by the concentration difference, the mixed alkali solution diffused to the water side solution. The two chambers were stirred by motors to avoid concentration polarization. After working for 1 hour, the solutions on both sides were poured out, and the NaOH concentrations on the alkali side and the water side were determined by acid-base titration with 0.1 M HCl solution, and the dialysis coefficient of hydroxide (U OH ), the concentration of Na2WO4 was determined by inductively coupled plasma atomic emission spectrometry, and the dialysis coefficient of tungstate (U W ), and then the separation coefficient (S) of the membrane is calculated by the formula.

[0031]

[0032] Where M is the amount of ions passing through, A is the effective mass transfer area (6.0 cm 2 ), t is the time, and represent the ion concentration of the diffusion solution at time 0 and time t, respectively. represents the ion concentration of the dialysate at time t. The separation coefficient of the membrane is OH - and WO4 2- The ratio of the dialysis coefficients, that is, S = U OH / U W。

[0033] After testing, the performance parameters of the SPES / MS cation exchange membrane obtained in this embodiment are: the dialysis coefficient of hydroxide (U OH ) is 0.01004m / h and the separation coefficient (S) is 26.2. Embodiment 2:

[0034] (1) Preparation of MS: 360 mL of deionized water and 11 mL of ammonia water were added to a 500 mL three-necked flask and mixed and stirred evenly. 0.8 g of the template agent CTAB was added and stirred at room temperature until it was completely dissolved. Then the temperature was raised to 60 °C, and 4 ml of TEOS was added dropwise for about 10 min. The mixture was magnetically stirred at 60 °C for 2 h, and then the stirring was turned off and the mixture was allowed to stand for 24 h. Finally, the obtained solution was centrifuged, filtered, dried, and then calcined in a muffle furnace at 550 °C for 6 h.

[0035] (2) Preparation of SPES: SSNa (1.0 g) and 73 mg of mesoporous silica (2% mass fraction) were weighed and added to DMAc (11 g), and dissolved and dispersed by ultrasound-assisted dissolution. Then, AA (0.67 g), MBA (83.3 mg), AIBN (33.4 mg) and PES (2 g) were added to the above solution, the temperature was raised to 70 °C, and the reaction was stirred for 24 h under a nitrogen atmosphere to obtain in situ cross-linked copolymerized polyethersulfone.

[0036] (3) Preparation of cation exchange membrane: The solution after the reaction in step 2 was placed in a vacuum oven at 25°C and evacuated for 30 min to remove bubbles. The film was then scraped on a glass plate with a 200 μm thick scraper. The glass plate was placed on a 60°C heating table. After the solvent was completely evaporated, the prepared membrane was repeatedly soaked and cleaned with deionized water to remove unreacted monomers. Finally, it was vacuum dried at 100°C to obtain the SPES / MS cation composite membrane.

[0037] The performance test is the same as in Example 1. After testing, the performance parameters of the membrane obtained in this example are: the dialysis coefficient of hydroxide (U OH ) is 0.00982m / h, and the separation coefficient (S) is 29.4. Embodiment 3:

[0038] The preparation method and performance test of the SPES cation exchange membrane in this embodiment are the same as those in Example 1, except that the mass of SSNa added in this embodiment is 1.67 g, and the mass of AA is 0 g (SSNa / AA: 10 / 0).

[0039] After testing, the performance parameters of the membrane obtained in this embodiment are: the dialysis coefficient of hydroxide (U OH ) is 0.01283m / h, and the separation coefficient (S) is 15.6. Embodiment 4:

[0040] The preparation method and performance test of the SPES cation exchange membrane in this embodiment are the same as those in Example 1, except that the mass of SSNa added in this embodiment is 1.34 g, and the mass of AA is 0.33 g (SSNa / AA: 8 / 2).

[0041] After testing, the performance parameters of the membrane obtained in this embodiment are: the dialysis coefficient of hydroxide (U OH ) is 0.00863m / h, and the separation coefficient (S) is 26.8. Embodiment 5:

[0042] The preparation method and performance test of the SPES cation exchange membrane in this embodiment are the same as those in Example 1, except that the mass of SSNa added in this embodiment is 0.67 g, and the mass of AA is 1 g (SSNa / AA: 4 / 6).

[0043] After testing, the performance parameters of the membrane obtained in this embodiment are: the dialysis coefficient of hydroxide (U OH ) is 0.00972m / h, and the separation coefficient (S) is 21.9. Embodiment 6:

[0044] The preparation method and performance test of the SPES cation exchange membrane in this embodiment are the same as those in Example 1, except that the mass of SSNa added in this embodiment is 0.33 g, and the mass of AA is 1.34 g (SSNa / AA: 2 / 8).

[0045] After testing, the performance parameters of the membrane obtained in this embodiment are: the dialysis coefficient of hydroxide (U OH ) is 0.00952m / h, and the separation coefficient (S) is 19.6. Embodiment 7:

[0046] The preparation method and performance test of the SPES / MS cationic composite membrane in this embodiment are the same as those in Example 2, except that the mass of MS added in this embodiment is 146 mg.

[0047] After testing, the performance parameters of the membrane obtained in this embodiment are: the dialysis coefficient of hydroxide (U OH ) is 0.01151m / h, and the separation coefficient (S) is 31.1. Embodiment 8:

[0048] The preparation method and performance test of the SPES / MS cationic composite membrane in this embodiment are the same as those in Example 2, except that the mass of MS added in this embodiment is 219 mg.

[0049] After testing, the performance parameters of the membrane obtained in this embodiment are: the dialysis coefficient of hydroxide (U OH ) is 0.01345m / h, and the separation coefficient (S) is 36.0. Embodiment 9:

[0050] The preparation method and performance test of the SPES / MS cationic composite membrane in this embodiment are the same as those in Example 2, except that the mass of MS added in this embodiment is 292 mg.

[0051] After testing, the performance parameters of the membrane obtained in this embodiment are: the dialysis coefficient of hydroxide (U OH ) is 0.01198m / h, and the separation coefficient (S) is 28.9.

Claims

1. A method for preparing a polyethersulfone / mesoporous silica interpenetrating network structure composite membrane, characterized in that: The polyethersulfone is mixed evenly with monomer acrylic acid, sodium p-styrene sulfonate and mesoporous silica nanoparticles, and then polymerized in situ to obtain a membrane liquid. After degassing and solvent volatilization, a composite cation exchange membrane is obtained.

2. The preparation method according to claim 1, characterized in that The steps include: Step 1: Preparation of MS CTAB was used as a template agent, dissolved in a mixed solvent of water and ammonia, and TEOS was used as a silicon source. Mesoporous silica nanoparticles were obtained by reacting at 60°C for 2h, and the template agent CTAB was removed by high-temperature calcination in a muffle furnace. Step 2: Preparation of SPES membrane solution Monomer sodium p-styrene sulfonate and mesoporous silica were added to DMAc, and ultrasonic-assisted dispersion and dissolution were performed. After complete dissolution, acrylic acid, polyethersulfone, crosslinking agent N, N-methylenebisacrylamide and initiator azobisisobutyronitrile were added in sequence, and the mixture was stirred and reacted at 70°C in a nitrogen environment for 24 h. Step 3: Preparation of composite cation exchange membrane The solution obtained in step 2 is placed in a vacuum oven, evacuated to remove bubbles, and the film is scraped on a glass plate. Finally, the glass plate is placed on a hot plate for heating. After the solvent is completely evaporated, the prepared membrane is repeatedly washed with deionized water to remove unreacted monomers, and vacuum dried to obtain a SPES / MS cationic composite membrane.

3. The preparation method according to claim 2, characterized in that: In step 1, the muffle furnace calcination temperature is 550°C and the time is 6 h.

4. The preparation method according to claim 2, characterized in that: In step 2, the mass ratio of polyethersulfone, sodium p-styrenesulfonate and acrylic acid is 6: 3: 2, and the mass ratio of MS addition is 2%-8%.

5. Use of the polyethersulfone / mesoporous silica interpenetrating network structure composite membrane prepared by the preparation method according to any one of claims 1 to 4 in alkaline diffusion dialysis.

6. The use according to claim 5, characterized in that: The polyethersulfone / mesoporous silica interpenetrating network structure composite membrane is used to separate hydroxide ions and tungstate ions by diffusion dialysis.